Electronic structure and stability of low symmetry Ta2O5polymorphs. Issue 6 (20th May 2014) - Kim, Ja‐Yong; Magyari‐Köpe, Blanka; Lee, Kee‐Jeung; Kim, Hyeong‐Soo; Lee, Seok‐Hee; Nishi, Yoshio
Abstract <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> The structures and electronic properties of Ta2O5 polymorphs were calculated using density‐functional theory employing the generalized gradient approximation with on‐site Coulomb corrections. Using this approach, a pseudo‐hexagonal structure was found to be a stable polymorph of Ta2O5 over δ‐ and β‐Ta2O5 and metastable relative to other recently proposed structures. Its diffraction spectrum and bandgap energy are in good agreement with experimental data. Therefore, the pseudo‐hexagonal structure might form in polycrystalline films and affect the switching process of resistive memory devices. Moreover, a neutral oxygen vacancy is found to induce an occupied defect state at 2.5 eV above the top of the valence band, in agreement with X‐ray photoelectron spectroscopy results. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)